Assessment of Atrial Electromechanical Delay and P‐Wave Dispersion in Patients with Psoriasis. Issue 9 (7th February 2014) - Yildiz, Abdulkadir; Ucmak, Derya; Oylumlu, Mustafa; Akkurt, Meltem Z.; Yuksel, Murat; Akil, Mehmet Ata; Acet, Halit; Polat, Nihat; Aydin, Mesut; Bilik, M. Zihni
<x xml:space="preserve">Abstract</x> Background In this study, we sought to evaluate atrial electromechanical properties and conduction homogeneity by tissue Doppler imaging and electrocardiography in patients with psoriasis. Methods Thirty‐four patients with psoriasis and 30 age‐ and gender‐matched healthy controls were included in the study. Atrial electromechanical coupling intervals were assessed by means of tissue Doppler echocardiography and P‐wave dispersion (Pd) was calculated from electrocardiogram. Results A total of 64 subjects (33 male) with a mean age of 36.8 ± 11.9 years were included in the study. Basal characteristics were similar between 2 groups. Intra‐atrial (15 ± 7 ms vs. 12 ± 5 ms, P = 0.009) and inter‐atrial (28 ± 7 ms vs. 23 ± 7 ms, P = 0.002) electromechanical delays were significantly higher in patients with psoriasis compared with control groups. P‐maximum (112 ± 16 ms vs. 103 ± 8 ms, P = 0.006) and Pd (35 ± 9 ms vs. 20 ± 6 ms, P < 0.001) were also prolonged in patients with psoriasis. Conclusion This study demonstrated that atrial electromechanical coupling intervals and P‐wave dispersion were prolonged in patients with psoriasis, which may cause an increased risk of atrial fibrillation in this patient group.